As raízes missioneiras da Quarta Colônia: recuperando o passado colonial - Janner, Tiago Luiz (2024)
The purpose of this dissertation is to review the historiography of the Fourth Colony. This action seeks to identify references to the missionary presence in the current regional territory. This is the problem that I intend to elucidate, rewriting the territory's past, considering the Fourth Colony as an area of Jesuit activity, analyzing texts, maps, letters, books, documents. After analysis of the history of the Fourth Colony, it was verified that there was practically no missionary theme in the region. This process can be understood as an “eraser”, erasing the presence of Spain and other peoples, present here long before European immigration. Cultural heritage is directly linked to research, as it is an integral part in forming the identity of the place. It is clear that published historiography and the common sense of the place tend to overvalue Germanness and Italianness, suppressing other cultural identities. Based on the principle of the “founding myth”, which is corroborated by the official websites of city halls, where immigration is shown to be the principle of occupation and formation, this being the “us”, with the history of the “other” in the background. I justify this research, because as an educator I work with the history of RS and the region, in which we can see the difficulty in understanding the theme of missions. To partially solve this problem, I proposed building an explanatory folder showing the missionary presence in the Quarta Colônia, to be distributed to culture centers, museums and teachers in the Quarta Colônia.